2021
DOI: 10.1177/10711007211007843
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Pain Interference Levels of Hallux Rigidus Patients Before and After Synthetic Cartilage Implant vs Arthrodesis Surgery

Abstract: Background: Hallux rigidus is a common and painful degenerative condition of the great toe limiting a patient’s physical function and quality of life. The purpose of this study was to investigate pre- and postoperative physical function (PF) and pain interference (PI) levels of patients undergoing synthetic cartilage implant hemiarthroplasty (SCI) vs arthrodesis (AD) for treatment of hallux rigidus using the Patient-Reported Outcomes Measurement Information System (PROMIS). Methods: PROMIS PF and PI t scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…The improvements were comparable to outcomes reported in the literature after MTP fusion, as previous studies also found significant improvement in PROMIS physical function at 38 months’ follow-up, which lends to the validity of our analysis. 15 The improvements seen in our study cohorts were also clinically significant when compared to estimated minimal clinically important difference (MCID) values of 4.5 for PROMIS physical function and 4.1 for PROMIS pain interference in a study of patients undergoing foot and ankle surgery. 13 Although there are no studies specifically estimating MCIDs after an MTP fusion, MCIDs for cheilectomy in patients with hallux rigidus have been reported.…”
Section: Discussionmentioning
confidence: 57%
“…The improvements were comparable to outcomes reported in the literature after MTP fusion, as previous studies also found significant improvement in PROMIS physical function at 38 months’ follow-up, which lends to the validity of our analysis. 15 The improvements seen in our study cohorts were also clinically significant when compared to estimated minimal clinically important difference (MCID) values of 4.5 for PROMIS physical function and 4.1 for PROMIS pain interference in a study of patients undergoing foot and ankle surgery. 13 Although there are no studies specifically estimating MCIDs after an MTP fusion, MCIDs for cheilectomy in patients with hallux rigidus have been reported.…”
Section: Discussionmentioning
confidence: 57%
“…The literature reports SCI procedures cause significantly less post-operative pain and significantly higher functional scores in the first six months post-surgery [ 11 , 23 ], with significantly reduced operative time and need for anesthesia [ 13 ], demonstrating a possibly faster initial recovery. However, these short-term benefits are found to reach no further significant difference at later follow-up (one and two years) [ 11 , 13 , 23 ] with evidence of significantly higher VAS pain scores in patients receiving an SCI [ 11 ]. The difference in rates of complication and adverse events requiring further treatment do not reach significance [ 11 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these short-term benefits are found to reach no further significant difference at later follow-up (one and two years) [ 11 , 13 , 23 ] with evidence of significantly higher VAS pain scores in patients receiving an SCI [ 11 ]. The difference in rates of complication and adverse events requiring further treatment do not reach significance [ 11 , 23 ]. Interestingly, Brandao et al reported no significant difference in FAAM sport scores and advised varying return to leisure activities, with patients undergoing arthrodesis more commonly returning to gym exercises, patients undergoing SCI more commonly returning to walking exercise and similar numbers returning to running [ 16 ], despite the known limitations on ROM following arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations